Desórdenes del sistema musculoesquelético por trauma acumulativo en estudiantes universitarios de computación e informática - Fonseca Barrantes, Melissa (Universidad de Costa Rica, 2011)
The main objective of this research was to establish the correlation of Musculoskeletal Disorders (MSD ́s) by accumulative damage, among university ́s students from the computer science school (ECCI) at the Universidad de Costa Rica (UCR). The study group included 129 computer users with an average age of 21,9 years old. Neck pain was the most commonly reported symptom (81 cases), followed by lumbar region (71 cases) and wrist pain (63 cases). The women perceived the higher stress, and the computer laboratory, followed by home environment, seem to have the higher risk factor associated with the symptoms. At least 90 % of students use the computer 6 or 7 days per week and 31 % report to use the computer 8 or more hours per day. In general, the symptoms increased according to the time of exposition. The level of perception of computer-‐‑related health risks among the students was low.